Changes in electrocorticographic beta frequency components precede spreading depolarization in patients with acute brain injury - Hertle, Daniel; Oberrauner, Marina; Santos, Edgar; Schöll, Michael; Diedler, Jennifer; Veltkamp, Roland; Unterberg, Andreas; Sakowitz, Oliver (Clinical neurophysiology, 2016)
Objective Spreading depolarization (SD) occurs after traumatic brain injury, subarachnoid hemorrhage, malignant hemispheric stroke and intracranial hemorrhage. SD has been associated with secondary brain injury, which can be reduced by ketamine. In this present study frequency bands of electrocorticographic (ECoG) recordings were investigated with regards to SDs. Methods A total of 43 patients after acute brain injury were included in this retrospective and explorative study. Relative delta 0.5-4 Hz, theta 4-8 Hz, alpha 8-13 Hz and beta 13-40 Hz bands were analyzed with regards to SD occurrence and analgesic and sedative administration. Higher frequencies, including gamma 40-70 Hz, fast gamma 70-100 Hz and high frequency oscillations 100-200 Hz were analyzed in a subset of patients with a sampling rate of up to 400 Hz. Results A close association of relative beta frequency and SD was found. Relative beta frequency was suppressed up to two hours prior to SD when compared to hours with no SD. This finding was partially explained by administration of ketamine. Even after removal of all patient data during administration of ketamine, SDs occurred predominantly during times with low relative beta frequency in a patient-independent analysis. Conclusion Suppression of beta frequency by ketamine or without ketamine is associated with low SD counts. Significance Alteration of beta frequency might help to predict occurrence of SDs in acutely brain injured patients.